Association between type of feeding at discharge from the hospital and nutritional status of very low birth weight preterm infants - Martins-Celini,F.P. (2018)
The ideal feeding for premature babies has been the source of extensive debate. The aim of this study was to assess the association between type of feeding at discharge and the nutritional status of very low birth weight infants. This was a retrospective cohort of preterm babies with birth weight ≤1500 g, born between January 2006 and December 2013. The infants were divided into 3 groups according to type of feeding at discharge: exclusive breast milk (group 1), mixed feeding (group 2) and exclusive artificial formula (group 3). Frequencies of each group were calculated, as well as mean Z-score differences in weight, length and head circumference. Six hundred and forty-nine newborns were included. The mean weight of groups 1, 2, and 3 was 1338.7, 1104.0, and 1254.7 g, respectively, and their mean gestational age was 31.9, 30, and 31.2 weeks, respectively. The Z-score differences (means±SD) for groups 1, 2, and 3 were: −0.84±0.68, −1.02±0.75, and −0.86±0.71 for weight, −0.21±1.23, −0.52±1.64 and −0.08±1.34 for head circumference, and −1.10±1.18, −1.54±1.37, and −0.97±1.21 for length. A significant difference was observed between groups 2 and 3 in the adjusted Z-score model for length, with no significant differences in anthropometric measurements for the other comparative analyses. Because of its many advantages, breastfeeding should be stimulated within neonatal units since nutritional status was not influenced by the different types of feeding.